Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/v14102299
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response after the Fourth Dose of SARS-CoV-2 mRNA Vaccine Compared to Natural Infection in Three Doses’ Vaccinated Solid Organ Transplant Recipients

Abstract: Solid organ transplant recipients (SOTRs) show higher rates of COVID-19 breakthrough infection than the general population, and nowadays, vaccination is the key preventative strategy. Nonetheless, SOTRs show lower vaccine efficacy for the prevention of severe COVID-19. Moreover, the emergence of new SARS-CoV-2 variants of concern has highlighted the need to improve vaccine-induced immune responses by the administration of repeated booster doses. In this study, we analyzed the humoral and cellular responses in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Based on these functional analyses, we have confirmed that responses triggered by the Spike protein from the Omicron BA.1 (B.1.1.529/BA.1) VoC are attenuated compared with its reference WT. These results go in line with the current knowledge (20, 26) and has prompted the recommendation of a second vaccine boost, in particular for patients endangered for severe COVID-19 such as patients receiving hemodialysis (25) or transplant recipients (44).…”
Section: Discussionsupporting
confidence: 85%
“…Based on these functional analyses, we have confirmed that responses triggered by the Spike protein from the Omicron BA.1 (B.1.1.529/BA.1) VoC are attenuated compared with its reference WT. These results go in line with the current knowledge (20, 26) and has prompted the recommendation of a second vaccine boost, in particular for patients endangered for severe COVID-19 such as patients receiving hemodialysis (25) or transplant recipients (44).…”
Section: Discussionsupporting
confidence: 85%
“…In this study, we found that post‐vaccine anti‐spike antibody responses were predominantly among participants with previous exposure to SARS‐CoV‐2. The impact of previous SARS‐CoV‐2 infection on antibody responses post‐vaccination is consistent with previous reports and highlights the need to consider alternative approaches to the standard vaccination series in kidney transplant recipients who are less likely to be responsive 19,20 . Although activated CD4 + and CD8 + T‐cell responses were observed across the cohort, further studies will be needed to determine whether these T‐cell responses were induced in an antigen‐specific manner (Figure S4).…”
Section: Discussionsupporting
confidence: 85%
“…The impact of previous SARS-CoV-2 infection on antibody responses post-vaccination is consistent with previous reports and highlights the need to consider alternative approaches to the standard vaccination series in kidney transplant recipients who are less likely to be responsive. 19,20 Although activated CD4 + and CD8 + T-cell responses were observed across the cohort, further studies will be needed to determine whether these T-cell responses were induced in an antigen-specific manner (Figure S4). Sattler et al utilized an activation-induced marker assay to monitor spike-specific CD4 + and CD8 + specific T cell responses in kidney transplant recipients 1 and 3 weeks post-second vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Although the benefit of a fourth dose in vulnerable subjects is clear, including for other categories of immunocompromised individuals, such as transplanted patients [ 32 ], the optimal boosting timing is still uncertain [ 33 ]. This issue is important to better define vaccination programs across different risk groups, not only frail patients.…”
Section: Discussionmentioning
confidence: 99%